-2(x-3)=2-(x+3)

Simple and best practice solution for -2(x-3)=2-(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x-3)=2-(x+3) equation:


Simplifying
-2(x + -3) = 2 + -1(x + 3)

Reorder the terms:
-2(-3 + x) = 2 + -1(x + 3)
(-3 * -2 + x * -2) = 2 + -1(x + 3)
(6 + -2x) = 2 + -1(x + 3)

Reorder the terms:
6 + -2x = 2 + -1(3 + x)
6 + -2x = 2 + (3 * -1 + x * -1)
6 + -2x = 2 + (-3 + -1x)

Combine like terms: 2 + -3 = -1
6 + -2x = -1 + -1x

Solving
6 + -2x = -1 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
6 + -2x + x = -1 + -1x + x

Combine like terms: -2x + x = -1x
6 + -1x = -1 + -1x + x

Combine like terms: -1x + x = 0
6 + -1x = -1 + 0
6 + -1x = -1

Add '-6' to each side of the equation.
6 + -6 + -1x = -1 + -6

Combine like terms: 6 + -6 = 0
0 + -1x = -1 + -6
-1x = -1 + -6

Combine like terms: -1 + -6 = -7
-1x = -7

Divide each side by '-1'.
x = 7

Simplifying
x = 7

See similar equations:

| 3d^2+5d-6=0 | | -16=x+23 | | 5x=9-3 | | -5-2x=3-6 | | 21x+30=20-3 | | x-6=.66666666666666y | | -5x+6=-9x+22 | | 19+x=-16 | | 3p=4q+r | | 2(x-2)^1/4-3=159 | | 2x+31-2x+25-3x=2x-31+10-21x | | 3x+1.5=3+2 | | x-6=1/3y | | 21i+4i= | | X+2x+17=104 | | x-8.7=-4.4 | | 45m=9 | | 2(x-6)=6-(x+8)+4 | | A=10h | | 4x+5-5x=-7 | | z-3/10=27/10 | | 8-n^2-7n=0 | | x-12-8=-1 | | n^2-12n=-36 | | 0.8(y+3)=4.8 | | 2x(5/35) | | 2-5/13=6/7 | | 53x-y=-7 | | w-7/9=2/3 | | x+5x+-4=18+-2x | | -2z+3=-4z+11 | | 2n+-9=n+6 |

Equations solver categories